(untitled) (Scientific journal of the Fergana State University, 2024)
This article devoted to the intricate interplay between language and culture through the lens of linguistic analysis, focusing specifically on the role of epithets. Epithets, characterized by their descriptive nature, carry profound linguistic and cultural significance, reflecting the values, beliefs, and societal norms of a particular culture. Through a comprehensive examination of linguocultural features associated with epithets, this article aims to elucidate their multifaceted functions and their implications for cross-cultural communication. Drawing upon linguistic theories and cultural studies, this research highlights the dynamic relationship between language and culture, shedding light on how epithets serve as vehicles for cultural expression and identity construction across diverse linguistic contexts.